Spatial analysis of Zika virus microcephaly cases in a Brazilian municipality - Daisyanne Augusto de Sales Santos; Maria Vera Lúcia Moreira Leitão Cardoso; Fernando Daniel de Oliveira Mayorga; Francisco Everson da Silva Costa; Natanael Nascimento Rodrigues; Gleicia Martins de Melo (Rev Rene, 2022)
Objective: to analyze the spatial distribution of microcephaly cases by Zika virus in a Brazilian municipality. Methods: ecological study that analyzed 53 confirmed cases of microcephaly by Zika virus, reported between 2015 and 2016, extracted from the Registry of Public Health Events - Microcephaly. Incidence rates of the disease in neighborhoods of the municipality, Global and Local Moran Index and Kernel dispersion method were calculated. Results: common areas with high Zika microcephaly incidence rates were identified. The value of Moran’s I demonstrated the presence of clusters, with p=0.001, I=0.3159 in 2015 and I=0.2158 in 2016. According to the Kernel map, there was concentration of cases in Regional Executive Secretariats IV and VI. Most of the cases are within or near precarious settlements. Conclusion: the cases did not occur randomly and reinforce their relationship with the living conditions of the population. Contributions to practice: it is expected that this study can contribute to reflect on public policies and surveillance actions to reduce Zika transmission, recognizing the territories of higher risk for the disease. In addition, to expand discussions between managers and health professionals to qualify notification, care, and monitoring of children with microcephaly by Zika.